Murine Precision-Cut Kidney Slices as an ex vivo Model to Evaluate the Role of Transforming Growth Factor-β1 Signaling in the Onset of Renal Fibrosis - Stribos, Elisabeth G. D.; Seelen, Marc A.; van Goor, Harry; Olinga, Peter; Mutsaers, Henricus A. M. (Frontiers in Physiology, 2017)
Renal fibrosis is characterized by progressive accumulation of extracellular matrix (ECM) proteins, resulting in loss of organ function and eventually requiring renal replacement therapy. Unfortunately, no efficacious treatment options are available to halt renal fibrosis and translational models to test pharmacological agents are not always representative. Here, we evaluated murine precision-cut kidney slices (mPCKS) as a promising ex vivo model of renal fibrosis in which pathophysiology as well as therapeutics can be studied. Unique to this model is the use of rodent as well as human renal tissue, further closing the gap between animal models and clinical trials. Kidneys from C57BL/6 mice were used to prepare mPCKS and slices were incubated up to 96h. Viability, morphology, gene expression of fibrosis (Col1a1, Acta2, Serpinh1, Fn1 and Pai-1), inflammatory markers (Il1b, Il6, Cxcl1), and protein expression (collagen type 1, α-smooth muscle actin, HSP47) were determined. Furthermore, to understand the role of the transforming-growth factor β (TGF-β) pathway in mPCKS, slices were incubated with a TGF-β receptor inhibitor (LY2109761) for 48h. Firstly, viability and morphology revealed an optimal incubation period of 48h. Secondly, we demonstrated an early inflammatory response in mPCKS, which was accompanied by subsequent spontaneous fibrogenesis. Finally, LY2109761 showed great antifibrotic capacity in mPCKS by decreasing fibrosis markers on mRNA level as well as by reducing HSP47 protein expression. To conclude, we here present an ex vivo model of renal fibrosis, which can be used to further unravel the mechanisms of renal fibrogenesis and to screen antifibrotic therapy efficacy.